Emotional intelligence (EI) at workplace : a study on Takaful Nasional's agents - Abang Sulaiman, b. Abg. Salleh. (Universiti Malaysia Sarawak (UNIMAS), 2002)
Emotional intelligence has been touted as the key to success in work. This paper looks into the concepts of emotional intelligence and its impact on insurance agents performance. The primary concern of this study is to relate emotional intelligence with work performance and how significant it is to work performance levels each agent possesses. Emotional intelligence and its relationship to low and higher work performance were examined among 37 Takaful Nasional agents of Kuching branch. Results showed that respondents with"high" Ellevels have pursued "high" work performance while majority of those who hold "low" El levels have been embedded in the "low" work performance.